Implementation of the sepsis risk score for chorioamnionitis-exposed newborns. (November 2018) - Gievers, Ladawna; Sedler, Jennifer; Phillipi, Carrie; Dukhovny, Dmitry; Geddes, Jonah; Graven, Peter; Chan, Benjamin; Khaki, Sheevaun
Abstract Background: To prevent early onset sepsis (EOS), ~10% of neonates receive antibiotics based on CDC recommendations regarding chorioamnionitis exposure. A sepsis risk score (SRS) predicts EOS and spares unnecessary evaluation and treatment. Local problem: Chorioamnionitis-exposed neonates utilize significant resources. Methods: An SRS algorithm was implemented to decrease resource utilization in chorioamnionitis-exposed neonates ≥35 weeks'. Outcome measures included antibiotic exposure, time in NICU, laboratory evaluations, and length of stay (LOS). Balancing measures were missed cases of EOS and readmissions. Data were assessed using run charts. Interventions: Plan-Do-Study-Act cycles were utilized to process map, implement and reinforce the algorithm. Results: A number of 356 patients met inclusion criteria. After algorithm implementation, antibiotic exposure reduced from 95 to 9%, laboratory evaluation from 96 to 22%, NICU observation from 73 to 10%. LOS remained unchanged. No missed cases of EOS, nor sepsis readmissions. Conclusions: Algorithm implementation decreased antibiotic and resource utilization without missing cases of EOS.